KOMUNIKASI ANTARPRIBADI SEBAGAI PEMBENTUK CITRA PUSTAKAWAN DI BAPUSIPDA - Santi Susanti (Jurnal Kajian Informasi dan Perpustakaan, 2015)
This research entitled Interpersonal Communication as image builder of Librarian at Bapusipda Jawa Barat. Conducted at Badan Perpustakaan dan Kearsipan Daerah (Bapusipda) Jawa Barat, this research is purposed to find out relation of nonverbal communication, send of message, technique of communication and frequency/ intensity at communication between librarian and users towards the image of librarian. This research used survey method with descriptive analysis. The data of this research is obtained from three sources: questionnaire, interview for primary data and literatures as secondary data. The technique used an accidental sampling. It requires 91 respondents. All results show that nonverbal communication, send of message, technique of communication done by librarian to their customers take the role towards the image building of librarian in Bapusipda, and frequency/ intensity of communication does not take enough role towards the image of librarian. The conclusion of this research are the aspects of interpersinal communication done by librarian to their customers take the role towards the image building of librarian in Bapusipda, nad the frequency/ intensity of communication does not take enough role towards the image of librarian.Penelitian berjudul “Komunikasi Antarpribadi sebagai Pembentuk Citra Pustakawan di Basusipda Jawa Barat”, dilakukan di Badan Perpustakaan dan Kearsipan Daerah (Bapusipda) Jawa Barat. Bertujuan untuk mengetahui kaitan komunikasi nonverbal, penyampaian pesan, cara berkomunikasi dan frekuensi/intensitas komunikasi pustakawan dengan pemustaka terhadap citra pustakawan. Metode yang digunakan dalam penelitian ini adalah survei, dengan jenis penelitian deskriptif. Data-data yang digunakan dalam penelitian ini diperoleh melalui tiga sumber, yaitu kuesioner, wawancara untuk data primer dan studi kepustakaan sebagai data sekunder. Teknik yang digunakan adalah accidental sampling dengan sampel 91 responden. Hasil yang diperoleh munjukkan bahwa komunikasi nonverbal, penyampaian pesan, cara berkomunikasi pustakawan dengan pemustaka berperan terhadap citra pustakawan di Bapusipda, Bandung. Sedangkan frekuensi/ intensitas komunikasi pustakawan kurang berperan terhadap citra pustakawan. Kesimpulan dari penelitian ini, aspek-aspek komunikasi antarpribadi berperan terhadap citra pustakawan di Bapusipda Bandung, sedangkan frekuensi/ intensitas komunikasi kurang berperan terhadap citra pustakawan.